Extra‐cerebral oxygenation influence on near‐infrared‐spectroscopy‐determined frontal lobe oxygenation in healthy volunteers: a comparison between INVOS‐4100 and NIRO‐200NX. (12th March 2014) - Sørensen, Henrik; Rasmussen, Peter; Siebenmann, Christoph; Zaar, Morten; Hvidtfeldt, Morten; Ogoh, Shigehiko; Sato, Kohei; Kohl‐Bareis, Matthias; Secher, Niels H.; Lundby, Carsten
Summary Introduction Frontal lobe oxygenation (ScO2) is assessed by spatially resolved near‐infrared spectroscopy (SR‐NIRS) although it seems influenced by extra‐cerebral oxygenation. We aimed to quantify the impact of extra‐cerebral oxygenation on two SR‐NIRS derived ScO2. Methods Multiple regression analysis estimated the influence of extra‐cerebral oxygenation as exemplified by skin oxygenation (SskinO2) on ScO2 in 21 healthy subjects exposed to whole‐body exercise in hypoxia (FiO2 = 12%; n = 10) and normoxia (n = 12), whole‐body heating, hyperventilation (n = 21), administration of norepinephrine with and without petCO2‐correction (n = 15), phenylephrine and head‐up tilt (n = 7). ScO2 was assessed simultaneously by NIRO‐200NX (SniroO2) and INVOS‐4100 (SinvosO2). Arterial (SaO2) and jugular bulb oxygen saturations (SjO2) were obtained. Results The regression analysis indicated that SinvosO2 reflects 46% arterial, 14% jugular, 35% skin and 4% oxygenation of tissues not interrogated. SinvosO2 follows a calculated estimate of cerebral capillary oxygenation (r = 0·67; P<0·0001). In contrast, the NIRO‐200NX‐determined ScO2 did not correlate with the estimate of cerebral oxygenation (r = 0·026; P = 0·71). Conclusion For all interventions, 35% of the INVOS‐4100 signal reflected extra‐cerebral oxygenation while, on the other hand, NIRO‐200NX did not follow changes in a calculated estimate of cerebral capillary oxygenation. Thus, the NIRO‐200NX and INVOS‐4100 do not provide for unbiased evaluation of the cerebral signal.